A systematic review of country-specific drivers and barriers to household food waste reduction and prevention - Chia, Dane *; Yap, Chin Choo *; Wu, Shin Ling *; Berezina, Elizaveta *; Aroua, Mohamed Kheireddine *; Gew, Lai Ti * (SAGE Publications, 2023)
Food waste is a global challenge that threatens the sustainable development of human societies. Although food waste is produced in all stages of the food supply chain, household food waste is the biggest contributor to the food waste fraction. In this research, we systematically reviewed 54 empirical studies to explore drivers and barriers to household food waste reduction and prevention. Key aspects, such as comprehension and perception of food waste issues, practices and lifestyles, were examined. Our findings suggest that a great understanding of the impact of one's food waste on health, environment and economy directly promotes food waste management. Additionally, the food waste issue is not attributed to a single factor, it may differ varies across countries. The majority of the reviewed literature on household food waste comes from European countries, where similar geographical, economic and cultural characteristics may lead to comparable drivers and barriers. This could be the reason for showing optimistic experience to the respective food waste management interventions. However, the applicability of these findings and interventions to regions beyond Europe are uncertain. Future studies should also be expanded to include regions such as Asia, North America, Africa, Oceania, Latin America and the Caribbean. To support the sustainable management of household food waste, mapping country-specific food waste determinants is crucial in developing easy-to-implement food waste interventions that can specifically address the food waste issue in each country.